UJI EFEKTIVITAS PENGGUNAAN AIR RENDAMAN DAUN KERING (Artocarpus Heterophyllus, Nephelium Lappaceum) DAN KUNING TELUR (Vitellus) TERHADAP JUMLAH TELUR AEDES sp YANG TERPERANGKAP - Jose A. Sjarkawi (POLTEKKES KEMENKES MANADO, 2011)
One method of controlling the Aedes sp without insecticides is the use of egg traps (Ovitrap). The purpose of this study to determine the effectiveness of the use of water soaking the dried leaves and egg yolk to the number of trapped mosquitoes Aedes sp. This type of research uses quasi-experiment. The subjects in this research that all the eggs of mosquitoes are found in this study ovitrap while the unit is a group of houses / buildings that occupy a certain area. Research sites is Perkamil District of Tikala Manado City as much as 8 houses, with replicates performed on each treatment was 3 times the replications. While the number of treatments is 3. So the number of objects that do research are 8 houses with 24 and 24 treatments in the treatment outside the home. Based on the results of the study the number of eggs of Aedes sp, amounting to 3216 grain 2289 grain yield of dried leaves (71%), water containing egg yolk amounted to 820 grains (26%), aquades 107 grains (3%). Based on the location of installation, which is placed outside the home ovitrap 2296 grain yield (71%), in the house of 920 points (29%). It can be concluded that the leaves dry more effectively with the number of eggs of Aedes sp trapped more than water that contains egg yolks and aquades. As a suggestion of water soaking the dried leaves can be disseminated to the public to always pay attention to the environment around the home of the bin of water, especially water that submerged the leaves dry.